Christianity and globalisation: An alternative ethical response - Müller, Retief (HTS teologiese studies, 2011)
This article critically evaluated the role of Christian Ethics in response to globalisation. It showed that ethical critiques of globalisation inevitably fall short when Christianity’s historical contributions to processes of globalisation are neglected or de-emphasised. A Christian Ethics that attempts completely to wash its hands of and disavow globalisation is therefore indicated to be perched on a false premise. In this regard, the author specifically discussed the divergent stances of Max Stackhouse and Rebecca Todd Peters and opted for the former as the more helpful when considered from an interdisciplinary approach. In the final analysis, the author argued that the problem of globalisation might fruitfully be addressed with an ethics that is not averse to bring the various insights of missiology, church history and practical theology to the table, focusing particularly on rituals of reconciliation and forgiveness.